Perception of the pest status of the oriental latrine fly (Chrysomya megacephala) and its control methods in Ogbomoso Agricultural Zone, Southwestern Nigeria - Ilesanmi Olatunji; Samuel Adelani Babarinde; Adeola Odewole (Wallacea Plant Protection Journal, 2026)
Chrysomya megacephala, known as the oriental latrine fly, thrives in human settlements and poses significant public health risks due to its role in spreading pathogens. This study assessed residents' perceptions of the pest status and control methods of C. megacephala in Ogbomoso Agricultural Zone, Nigeria. Two Local Government Areas, Ogbomoso North and Surulere, were purposively selected. Using a snowball technique, 192 respondents were interviewed through a structured questionnaire, gathering data on socio-economic characteristics, awareness, perceptions, control methods, and the pest’s significance. Descriptive statistics were used for analysis. Findings showed that 61.5% of respondents were male, suggesting male dominance in livestock rearing and processing, which attracts blowflies. The mean respondent age was 51.7 years. A high level of awareness (82.8%) of C. megacephala was observed. Residents perceived the fly as a serious pest; its infestation of wounded animals, reducing their economic value, and its role in transmitting cholera via contaminated meat ranked highest (WMS = 4.3). Other impacts included causing typhoid and animal weight loss (WMS = 4.1). In terms of control, 87.0% preferred chemical methods, 77.0% preferred botanicals, and 34% preferred biological control agents, while 33% preferred physical control. Although C. megacephala was viewed as a pollinator (83.3%), a large proportion of the respondents viewed it as a health threat (77.6%) and disease vector (67.7%). Therefore, the study recommends promoting eco-friendly alternatives to chemical control, such as botanical and cultural controls, to enhance human well-being and reduce public health risks connected to C. megacephala in Ogbomoso Agricultural Zone, Nigeria.